Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1517717
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence of cubic boron nitride films deposited by chemical vapor deposition

Abstract: Articles you may be interested inMorphology dependence of cathodoluminescence from cubic boron nitride films deposited by chemical vapor deposition J. Appl. Phys. 99, 124915 (2006); 10.1063/1.2205356 Ion implantation effects on the structure and nanomechanical properties of vapor deposited cubic boron nitride films J.Electron cyclotron wave resonance plasma assisted deposition of cubic boron nitride thin films Cubic boron nitride thin film deposition by unbalanced magnetron sputtering and dc pulsed substrate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…5(b)). The vibration energy of the phonon participated was lower than the energies of the characteristic cBN optical phonons (131 meV for TO and 162 meV for LO mode [39]). However, it was equal to LO 3 phonon energy of hBN crystal lattice (LO 3 = 828 cm −1 (102.6 meV)) [40].…”
Section: Resultsmentioning
confidence: 90%
“…5(b)). The vibration energy of the phonon participated was lower than the energies of the characteristic cBN optical phonons (131 meV for TO and 162 meV for LO mode [39]). However, it was equal to LO 3 phonon energy of hBN crystal lattice (LO 3 = 828 cm −1 (102.6 meV)) [40].…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the deposition of such thick films, even if the processes used are not suited for industrial applications, allowed the application of a wide variety of characterization methods which require a certain thickness and which cannot be applied to the standard c-BN films of a few hundred nm at best. Techniques such as Raman spectroscopy [10,26,12], cathodoluminescence [27], or advanced mechanical/tribological testing [15,23,25] to name but a few, have indeed revealed a vast amount of valuable informations on the properties of c-BN films, but also on the growth mechanisms.…”
Section: Literature Survey: Deposition Of Thick C-bn Filmsmentioning
confidence: 99%
“…Zhang et al 244 reported the cathodoluminescence characteristics of different c-BN samples. A, B, C were deposited by dc jet plasma CVD using a gas mixture of Ar-N 2 -BF 3 -H 2 with film thicknesses measured at about 10, 3, and 2 nm, respectively and sample D was deposited by microwave plasma CVD using a gas mixture of He-N 2 -BF 3 -H 2 of thickness about 3 nm.…”
Section: Optical Propertiesmentioning
confidence: 99%